2005
DOI: 10.1093/toxsci/kfi261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TCDD and PCB CYP1A Induction Sensitivities in Fresh Hepatocytes from Human Donors, Sprague-Dawley Rats, and Rhesus Monkeys and HepG2 Cells

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) and related chemicals induce cytochrome P450 1A (CYP1A) gene expression and, at sufficient exposures, cause toxicity. Human health risks from such exposures are typically estimated from animal studies. We tested whether animal models predict human sensitivity by characterizing CYP1A gene expression in cultures of fresh hepatocytes from human donors, rats, and rhesus monkeys and HepG2 human hepatoma cells. We exposed the cells to three aryl hydrocarbon receptor (AhR) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 39 publications
7
39
2
Order By: Relevance
“…In addition, because the induction of CYP1A1 is minimal in human livers (Xu et al, 2000;Silkworth et al, 2005) and deltamethrin is predominately metabolized by esterases in humans, CYP1A1 metabolism is less interesting for the purposes of this study. Because of the minimal metabolism of both deltamethrin and esfenvalerate by human CYP3A4, kinetic parameters were not determined for this P450.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because the induction of CYP1A1 is minimal in human livers (Xu et al, 2000;Silkworth et al, 2005) and deltamethrin is predominately metabolized by esterases in humans, CYP1A1 metabolism is less interesting for the purposes of this study. Because of the minimal metabolism of both deltamethrin and esfenvalerate by human CYP3A4, kinetic parameters were not determined for this P450.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Silkworth et al (2005) found that human cells are about 10-1000 times less sensitive to TCDD, PCB-126, and Aroclor 1254 than are rat and monkey cells. Importantly, the newly calculated rat-human interspecies relative potency factors for PCB-126 were more than 100 times lower than the current rodent-derived value (Silkworth et al, 2005).…”
Section: (C) Validation In Experimental Systemsmentioning
confidence: 98%
“…AhR activation by DL-PCBs has been reported in many studies in vitro and in vivo, including comparative toxicogenomic analyses in primary human, monkey, and rodent hepatocytes (Silkworth et al, 2005;Westerink et al 2008). In a comparative in-vitro study in primary cultures of human and rat hepatocytes exposed to TCDD or PCB-126 at various concentrations for 48 hours, dose-responses and relative effective potencies (REP-values) were calculated for induction of CYP1A1 and other AhR-responsive genes (Carlson et al, 2009).…”
Section: (C) Validation In Experimental Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the mechanistic relationship of PCBs to tumorigenesis in animals is due solely to aryl hydrocarbon hydroxylase pathways also remains speculative; non -aryl hydrocarbon hydroxylaseinducing congeners can behave as tumor promoters (104). The TEF approach assumes that there is no interspecies difference in toxicity, which is not true (105,106), and some data show that humans are less sensitive than rodents (107). Also, enzymatic induction can vary depending on tissue and dose (108).…”
Section: Toxic Equivalency Factorsmentioning
confidence: 99%